Hydrogen sulfide releasing compounds : synthesis,characterization and anti-cancer effect study - Song, Zhijian (2014)
Recent studies have shown hydrogen sulphide (H2S) as a promising gas mediator, which has versatile bio-functions, such as cardiovascular protection, nervous system protection, anti-tumour, ion-channel regulation, and so on. It is believed that garlic’s health function is closely related to the H2S releasing property of its organosulfur compounds. However, H2S releasing compounds extracted from plants are neither stable nor in high enrichment. Hence, people are paying attention to artificially synthesized H2S donors, which may have potential medicinal value. Based on the current structures of some natural products, we developed a series of novel H2S releasing compounds and studied their structure activity relationship.